Teaching New Vocabulary to Iranian Young FL Learners: Using Two Methods Total Physical Response and Keyword Method - Amir Toghyani Khorasgani (Institute of Advanced Engineering and Science, 2017)
Early language learning for children is increasingly common, and the majority of parents and the public do not see it as superfluous or overburdening children. Moreover, teaching a foreign language to very young children has been an increasingly dominant trend in most globalized societies. While there is abundant literature that supports teaching a foreign language at an early age through language immersion programs, little is known about the efficiency of strategies used to explicitly teach new vocabulary words in a foreign language to young learners. This empirical investigation aimed to assess and compare the efficiency of two mnemonics that have been traditionally used to explicitly teach new foreign language words: the Keyword Method (KWM) and the Total Physical Response (TPR). Results indicate that the KWM is more effective than TPR in teaching new vocabulary words in a foreign language to early elementary school children.